Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.

Amino functionalized zeolitic tetrazolate framework (ZTF) with high capacity for storage of carbon dioxide - Panda, Tamas; Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemical Communications, 2011)
A three dimensional -NH(2) functionalized Zeolitic Tetrazolate Framework (ZTF-1) has been reported. The framework adopts a dia topology (M-L-M angle is close to 156 degrees). ZTF-1 shows high CO(2) (273 K) and H(2) (77 K) uptake due to the presence of the free -NH(2) group and uncoordinated tetrazolate nitrogen.

Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

Template induced structural isomerism and enhancement of porosity in manganese(II) based metal-organic frameworks (Mn-MOFs) - Panda, Tamas; Pachfule, Pradip; Banerjee, Rahul (Chemical Communications, 2011)
Three new metal-organic framework isomers have been synthesized by using the organic linker 5-triazole isophthalic acid and Mn(NO3)(2)center dot xH(2)O. Structural conversions from non-porous to porous MOFs due to the template effect have been observed. The cross-sectional pore apertures of the resulting Mn-MOFs are comparable to the molecular dimensions of the template (pyrazine and 4,40-bipyridine). The periodic increased porosity in Mn-MOFs depending on the size of the template used has been further confirmed by the CO2 adsorption isotherms.

Fine-tuning the balance between crystallization and gelation and enhancement of CO2 uptake on functionalized calcium based MOFs and metallogels - Mallick, Arijit; Schoen, Eva-Maria; Panda, Tamas; Sreenivas, K.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry, 2012)
The synthesis, structure, gas adsorption and catalytic properties of a new 3D porous, crystalline metal-organic framework (Ca-5TIA-MOF) as well as stable viscoelastic metallogels (Ca-5TIA-Gel) are reported. Remarkably, the preparation of both types of materials can be carried out starting from the same organic ligand (i.e. 5-(1,2,4-triazoleyl) isophthalic acid (5TIA)), divalent metal ion (i.e. Ca(II)) and organic solvent (i.e. DMF). In this particular case, the presence of water in the solvent system favors the formation of a crystalline MOF, whereas a pure organic solvent induces gelation. The characterization of the materials was carried out using a series of techniques including XRD, FT-IR, TGA, TEM, SEM, SAXS and dynamic rheology. Experimental PXRD peaks of both Ca-5TIA-xerogel and Ca-5TIA-MOF matched reasonably well with simulated PXRD, suggesting the presence of, at least, some common structural elements in the 3D networks of both xerogel and crystalline phases. Moreover, the nature of the metal counteranion was found to have a critical influence on the gelation phenomenon. To the best of our knowledge, this report describes unprecedented Ca-based LMW-metallogels, as well as the first porous Ca-based MOF, which shows adsorption capacity for CO2 at 1 atm pressure. Interestingly, Ca-5TIA-xerogel presented 20% higher CO2-uptake than the crystalline Ca-5TIA-MOF at 1 atm and 298 K. Both Ca-5TIA-MOF and Ca-5TIA-Gel also displayed a modest catalytic activity towards the hydrosilylation of benzaldehyde, with slightly better performance for the gel phase material.

Self-assembled one dimensional functionalized metal-organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In-and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 x 10(-5) and 3.61 x 10(-3) S cm(-1) respectively.

Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability - Biswal, Bishnu P.; Panda, Tamas; Banerjee, Rahul (Chemical Communications, 2012)
Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.

Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.

Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.

High charge carrier mobility in two dimensional indium (iii) isophthalic acid based frameworks - Panda, Tamas; Banerjee, Rahul (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2014)
The effect of dimensionality (1D to 2D) on charge carrier mobility have been studied thoroughly on three In(III)-isophthalate based MOFs [In-IA-1D, In-IA-2D-1 and -2]. In-IA-1D possess 1D nanotubular architecture with [(CH3)(2)NH2](+). In-IA-2D-1 have 2D layers containing only [(CH3)(2)NH2](+) cations. Whereas, In-IA-2D-2 have [(CH3)(2)NH2](+) cations as well as solvent DMF molecule inside the crystal structure. Due to presence of the pi-pi stacking arrangement among the phenyl rings of IA moieties facilitates the high charge carrier mobility (4.6 x 10(-3) cm(2) V-1 s(-1) at V-G = -40 V) in In-IA-2D-2. However, In-IA-1D and In-IA-2D-1 does not show any charge carrier mobility due to absence of pi-pi stacking arrangement.
Keywords: Charge carrier mobility; Coordination chemistry; metal organic framework; pi-pi stacking

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.

Robust zeolitic tetrazole framework for electrocatalytic dopamine detection with high selectivity - Sarfudeen, Shafeeq; Sruthi, Vadakke Purakkal; Maibam, Ashakiran; Panda, Premchand; Jhariat, Pampa; Senthilkumar, Sellappan; BabaRao, Ravichandar; Panda, Tamas (Inorganic Chemistry, 2023)
A novel zeolitic tetrazolate framework (ZTF-8) has been synthesized by solvent-free heat-assisted (70 C-degrees) mechanochemical grinding of zinc acetate and 5-methyl tetrazole in the presence of NaOH powder. The structure of ZTF-8 adopts the zeolitic sodalite (SOD) topology with uncoordinated N-heteroatom sites and resembles the structure of the well-known zeolitic imidazole framework ZIF-8. ZTF-8 is exceptionally stable in 0.1 M aqueous acid and base solutions for 60 days at 25 C-degrees. The unique structure with uncoordinated N-heteroatom active sites and exceptional stability of ZTF-8 facilitated the electrocatalytic oxidation of dopamine to dopamine quinone at neutral pH. Without any postsynthetic modification, ZTF-8 is directly used for the facile electrochemical detection of dopamine over a wide range of concentrations (5-550 mu M) with a high sensitivity (2410.8 mu A mM-1 cm-2). It also demonstrated promising selectivity over other interferents of similar oxidation potential, such as ascorbic acid and uric acid. The DFT study revealed that the ZTF-8 framework has a higher binding energy (-145.07 kJ/mol) and stronger interaction with dopamine than its isostructural ZIF-8 structure (-130.42 kJ/mol).